Portfolio structures: Can they contribute to solving the low-risk puzzle? - Tobias Hiller (Managerial and Decision Economics, 2023)
This article expands on previous studies of the so-called low-risk puzzle with concepts from cooperative game theory. To allocate portfolio risk to single assets, previous studies used concepts such as the Shapley value. In these concepts, the marginal contributions of assets to risks of subsets of the portfolio are used to allocate portfolio risk to assets. In this article, beyond the marginal contributions, a structure on a set of assets is considered in the allocation of portfolio risk. This structure can model the branch, firm size or the region of the assets. Specifically, the Myerson value and the Spectrum value of cooperative game theory are applied. We show the application by means of a simulation study. In this context, considering an additional structure could enhance the analysis of the so-called low-risk puzzle.
Keywords: 650